Comparison of antimicrobial activity of three commercially used quaternary ammonium surfactants - Krasowska, Anna; Biegalska, Anna; Łukaszewicz, Marcin (2012)
Abstract Background Quaternary ammonium salts (QASs) formulations are the disinfectants of choice for hospitals. The advantage of formulation containing QAS is the possibility of their usage as rinse free solutions e.g. for hands. Long lasting and widespread industrial usage of (QAS) increase number of resistant pathogens not only to these but also other drugs. Thus, it is important to elucidate the chemical composition – activity relationships in order to create highly effective mixtures having synergistic activity. Material and Methods Antimicrobial activity of three different quaternary ammonium salts (cocamidopropyl betaine, dimethyl amine oxide and benzalkonium chloride) have been tested separately and as mixtures. Experiments were performed according to CSN PN-EN Standards on reference strains. Minimal inhibitory concentrations (MIC) were obtained for Escherichia coli ATCC 10536 (PCM 1144), Enterococcus hirae ATCC 10541 (PCM 2559), Staphylococcus aureus ATCC 6538 (PCM 2602), Pseudomonas aeruginosa ATCC 15442 (PCM 2563), Candida albicans (ATCC 10231) and Listeria monocytogenes. Results The highest antimicrobial activity had benzalkonium chloride, the lowest activity cocamidopropyl betaine. Mixtures showed increased antimicrobial activity. Conclusions For the tested compounds there is positive correlation between critical micelle concentration and activity. Synergistic activity was found for mixture of compounds.
Keywords: minimal inhibitory concentration; bacteria; quaternary ammonium salts; yeast